Traditional Institutions and Two-Way Communication in Addressing Violence Against Women in Farming Families: A Case Study in Sigi Regency - Bangkele, Elli Yane; Munir, Muh Ardi; Sumarni, Sumarni (Journal of Health and Nutrition Research, 2025)
Violence against women is a major public health problem globally and in Indonesia. This study aimed to determine the handling of violence against women in farming families through a two-way communication approach based on traditional institutions in Sigi Regency, Central Sulawesi. This qualitative study employed a two-way communication approach. Key informants included traditional figures (head of the Traditional Institution and several additional informants involved in and knowledgeable about violence against women in farming families, including village heads, hamlet heads, community leaders, women's figures/activists, religious leaders, and traditional leaders in Sigi Regency). The main instrument was an interview guideline, and the data were analyzed using qualitative descriptive analysis. The causes of violence against women in farming families in Sigi Regency, Central Sulawesi Province, were identified as economic problems, patriarchal culture, and education. Impacts experienced by victims included: psychological trauma (frustration, heartache, shame, mental pressure), physical trauma (bruises, wounds), family neglect (lack of support), and separation (divorce). Regarding the prevention of violence against women in farming families, the findings indicate that efforts focused on intervention after violence occurred, rather than proactive prevention. In terms of handling violence, two patterns emerged: initial handling by the family using a familial approach, and subsequent reporting through government channels (such as the village office followed by customary law) if the violence persisted or the familial approach was unsuccessful. Alternatively, some cases were directly reported to the village office without family negotiation